2003
DOI: 10.1073/pnas.1533135100
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the size of nanoscale toroidal DNA condensates with static curvature and ionic strength

Abstract: The process of DNA condensation into nanometer-scale particles has direct relevance to several fields, including cell biology, virology, and gene delivery for therapeutic purposes. DNA condensation has also attracted the attention of polymer physicists, as the collapse of DNA molecules from solution into well defined particles represents an exquisite example of a polymer phase transition.Here we present a quantitative study of DNA toroids formed by condensation of 3 kb DNA with hexammine cobalt (III). The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
190
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(204 citation statements)
references
References 36 publications
13
190
1
Order By: Relevance
“…The structures of the cation-MT bundle phases are not sensitive to the concentration of condensing cation when all MTs are in the bundle phase, unlike what has been recently observed for DNA with low ionic strength (31). However, the addition of monovalent salt dramatically affects the MT bundles and causes the MT-MT spacing to swell (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…The structures of the cation-MT bundle phases are not sensitive to the concentration of condensing cation when all MTs are in the bundle phase, unlike what has been recently observed for DNA with low ionic strength (31). However, the addition of monovalent salt dramatically affects the MT bundles and causes the MT-MT spacing to swell (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Toroids of size larger than ∼200 nm have been observed. In a detailed study [17], the toroid mean diameter was found to vary between 30 and 100 nm depending on the solution conditions, while the toroid thickness was in the range from 10 to 70 nm. The geometry of a toroid can be characterized by the ratio between its thickness and its diameter.…”
mentioning
confidence: 99%
“…5, we show some experimental data for the maximum thickness to diameter ratio (data extracted from Ref. [17]) under var- [17]. For a given condensation condition (see legend), we take only the point with the maximum thickness to diameter ratio.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] A few recent experiments concentrated on the kinetics of DNA compaction. They showed that DNA condenses continuously and linearly with time once the compaction process begins.…”
mentioning
confidence: 99%